Caracterização de Aspergillus spp. no cenário clínico brasileiro, modelos experimentais de aspergilose invasiva e avaliação farmacológica dos novos compostos F901318 e APX001A - Negri, Clara Ezequiel [UNIFESP] (2017)
Aspergillus is a mould genus frequently isolated in cases of fungal infections among patients at tertiary hospitals worldwide. Currently, the genus is composed of about 350 species, being more than 40 already described as a human pathogen in diverse clinical syndromes. In general, A. fumigatus is the most prevalent species causing invasive aspergillosis (IA) in Brazil and worldwide. The Brazilian scenario regarding cryptic and rare Aspergillus species presenting intrinsical resistance to antifungal drugs, as well as A.fumigatus resistance to triazoles is not known. Due antifungal resistance reported in some countries, multiple drug-drug interactions and considerable toxicity of Amphotericin B, new compounds, with new therapeutical targets are urgently required. In addition, there is also interest for experimental models standardization that allows the determination of pharmacokinetics (PK) and pharmacodynamics (PD) parameters associating efficiency of the drug in different therapeutic regimens. Therefore the articles presented in the present study aims to characterize Aspergillus species distribution and susceptibility profile in the Brazilian clinical scenario, verify the presence of acquired triazole resistance, developed new experimental IA models applied to analyses of therapeutic response and evaluate PD of two new compounds, F901318 (F2G Ltd) and the active moiety APX001A (APX001 pro-drug) (Amplyx Ltd) using a diversity of IA experimental models. Article 1: The purpose of this study was to analyse the distribution of cryptic and rare Aspergillus species among clinical samples from 133 patients admitted in 12 medical centres in Brazil and to analyse the in vitro activity of different antifungal drugs. The identification of Aspergillus species was performed based on a polyphasic approach, as well as sequencing analysis of the ITS region, calmodulin and β-tubulin genes and phylogenetic analysis when necessary. The in vitro susceptibility tests with voriconazole, posaconazole and itraconazole were performed according to the CLSI M38-A2 document (2008). We were able to demonstrate a high prevalence of cryptic species (19%) causing human infection, and three isolates represented by species A. thermomutatus, A. ochraceus and A. calidoustus showed less in vitro susceptibility to at least one of the triazoles tested. Article 2: Here we evaluated the in vitro antifungal susceptibility of 221 clinical A. fumigatus isolate, from 6 medical centres in Brazil according to CLSI M38 A-2 guidelines. Sixty-one isolates (27%) exhibiting MIC xix at the epidemiological cut-off value (ECV) for itraconazole or above ECV for any triazole were checked for CYP51A mutations. No mutations were documented, indicating that triazoles may be safely used to treat aspergillosis in Brazil. Article 3: F901318 (F2G Ltd) is the leading representative of a novel class of drug, the orotomides, is an antifungal drug in clinical development. Novel experimental in vitro (static and dynamic) and in vivo (murine) models of sinopulmonary infections caused by A. flavus were developed to evaluate F901318 PD using galactomannan (GM) and histopathology as models’ readout. Mathematical models were used to correlate F901318 exposure-response. All novel experimental models demonstrated to be an efficient tool for pharmacological analyses of antifungal drugs. F901318 is a potential new agent for the treatment of invasive infections caused by Aspergillus flavus with PDs that are comparable to other first-line triazole agents. Article 4: APX001A (Amplyx Ltd) is the active moiety of the new compound APX001, with action in the fungus cell wall. The pharmacodynamic of APX001A was analysed according to EUCAST susceptibility tests and in a static in vitro model of IPA caused by an A. fumigatus wild-type strain as well as strains carrying mutations related to triazole resistance. Galactomannan index (GMI) was used as PD readout. The Minimal effective concentration of 0.03 mg/L was obtained for all isolates and the concentration-dependent decline was observed in a static model, which ≤ 0.5 mg/L caused near maximal GMI suppression in the endothelial compartment of the static model for all isolates tested, showing a potential use of APX001 for IPA treatment.